A Quantitative Study of Oil Price Decrease and Bankruptcy Probability in Oil and Gas Companies - Rosdini, Dini; Nautika, Rahardi Gita (International Research Journal of Business Studies, 2019)
The decrease of oil prices globally has an impact on oil and gas company’s financial health. This study aims to provide empirical evidence about the effect of oil prices on the probability of bankruptcy in Indonesia, Singapore, and Australia using the probability of bankruptcy model of Altman Z-Score. The price of oil is measured by the price of Brent crude. Our sample is made of 20 oil and gas firms listed at the Indonesia Stock Exchange (IDX), the Australian Securities Exchange (ASX) and the Singapore Exchange (SGX) during the period of 2013- 2015 selected through purposive sampling. This study is a quantitative research with secondary data analyzed using simple regression model. The results of this study indicate that oil prices significantly influence the bankruptcy probability of oil and gas companies in Indonesia, Singapore, and Australia.